DEVELOPMENT OF A DUAL-SYSTEM SCHOOL MANAGEMENT MODEL FOR THE KINGDOM OF CAMBODIA* - Pech, Seang; Siribanpitak, Pruet; Sumettikoon, Piyapong (Scholar: Human Sciences, 2015)
The objectives of this descriptive research study were 1) to study the current and desirable status of dual-system school management of the Kingdom of Cambodia; 2) to analyze the priority needs to rectify the dual-system school management for the Kingdom of Cambodia; and 3) to develop a management model for dual-system school for the Kingdom of Cambodia. This research study employed the research and development method (R&D). The data of the current and desirable status of dual-system school management were collected from 540 respondents from 3 dual system schools. The respondents were 11 school administrators, 165 teachers, 34 school committees and 330 students. To validate the draft of a dual system school management model, 42 experts and stakeholders were invited for individually validation and other 20 Cambodian experts and stakeholders were also invited to small group discussion. The collected data were analyzed using descriptive statistics, and the formula of PNI modified was also used to find the priority need index level. The findings revealed that 1) the mean of the current status of dual-system school management of the Kingdom of Cambodia was high where Formal Model (